Opinions and Feelings: The Validity of Attitudes toward Computers - Alexander, Mary Jane (1984)
Because the human-machine interface has been problematic in the introduction of automation into health care, considerable attention has been paid to users' attitudes. However, data presented here on the impact in 13 state psychiatric facilities of an automated prescription review system show no relationship between clinician acceptance of the system and improved prescribing practices. Effective evaluation research requires that construct and predictive validity of attitude measures be established rather than assumed. We need to know which attitudes (representing clearly defined constructs) of which relevant users bear any systematic relationship to the quality or efficiency of care.